Screening and diagnostic assessment of neurodevelopmental disorders in a male prison. (9th June 2015) - McCarthy, Jane; Chaplin, Eddie; Underwood, Lisa; Forrester, Andrew; Hayward, Hannah; Sabet, Jessica; Young, Suzy; Asherson, Philip; Mills, Richard; Murphy, Declan
Abstract : Purpose: – The purpose of this paper is to identify neurodevelopmental disorders and difficulties (NDD) in a male prison. The study used standardised tools to carry out screening and diagnostic assessment of the attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and intellectual disability (ID). Design/methodology/approach: – The ADHD self-report scale, 20-item autism quotient and the Learning Disability Screening Questionnaire were used to screen 240 male prisoners. Prisoners who screened positive on one or more of these scales or self-reported a diagnosis of ADHD, ASD or ID were further assessed using the diagnostic interview for ADHD in adults, adapted Autism Diagnostic Observation Schedule and the Quick Test. Findings: – Of the 87 prisoners who screened positive for NDD and were further assessed, 70 met the study's diagnostic criteria for ADHD, ASD or ID. Most of those with NDD (51 per cent) had previously gone unrecognised and a high proportion (51 per cent) were identified through staff- or self-referral to the study. Originality/value: – The study demonstrated that improving awareness and providing access to skilled, standardised assessment within a male prison can result in increased recognition and identification of NDD.